Characterization of consumption of vegetables in the families of the south-south of Costa Rica. - Villalobos-Monge, Alexis (2013)
The objective of this work was to determine the various quantitative and qualitative aspects that explain the culture of vegetable consumption of families living in the socalled south-south region of Costa Rica. This work presents results from the characterization of horticulture products consumption culture performed in 2011 amongst families that live in the region known as south-south Costa Rica. Through surveys applied to a stratified sample of families, market prices were determined for home consumption of these foods, which determined a maximum value of US$1,74 million per week, where the main items of consumption according to the amount paid would be the tomato, potato, plantain, onion and broccoli to name the top five. Qualitative assessments of the consumption of these products were also possible to establish, for example, 71.2% of families in the study area indicated that freshness was the most valuable property for purchase, amongst other traits such as the main place to acquire these foods, were the supermarket was the most common corresponding to 38.4% of cases.